An adhesive, its preparation method and its uses
By dispersing polymer polymers and underwater adhesion molecules with high dielectric constant, and forming a network structure through metal ion coordination, the problem of water film affecting adhesion effect in underwater environment is solved, and underwater Effective adhesion and coverage.
Patent Information
- Application Number
- CN202110184361.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-08
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-02-08
AI Technical Summary
The existing underwater adhesive loses adhesion effect due to the presence of water film in the underwater environment, and the polymer modification is cumbersome and the synthesis is complex, making it not suitable for large-scale industrial production.
Use a water-soluble solvent with a dielectric constant ≥30 as a dispersant to disperse polymers and underwater adhesion molecules, and form an interpenetrating network through the coordination of metal ions to realize underwater or in a wet environment. effective adhesion.
The covering and adhesion of the target substrate in underwater or in water-wet environments is achieved, and the influence of water film on the adhesion effect is overcome. The process is relatively simple and suitable for large-scale industrial production.
Smart Images

Figure CN114907793B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of adhesives, and specifically relates to an adhesive that can be used underwater or in a water-wet environment, a preparation method thereof, and its uses and use methods, and further relates to an adhesive that can be used underwater or in a water-wet environment and is designed based on the principle of interface instability, and its preparation method, and its uses and use methods. Background Art
[0002] Due to the potential applications of underwater adhesives in the fields of biomedicine, environmental protection and industrial production, the research on underwater adhesives has received extensive attention. Ordinary commercial glues are often required to be used in a dry environment. Due to the presence of adsorption and bonding water layers on the solid surface in the water environment, the contact between the current commercial adhesives and the solid surface is hindered, causing the adhesive's adhesion to gradually weaken or even disappear underwater, because the presence of water will seriously damage its adhesion effect.
[0003] At present, inspired by marine organisms, the design and preparation of underwater adhesives mainly focus on the design of adhesion molecules (catechol or dopamine) and the functional modification of adhesives. Inspired by the adhesive proteins of marine organisms, people use catechol or dopamine, which are rich in them, as functional groups to modify different polymer chains in order to improve their underwater adhesion properties. However, the preparation of polymer modification is cumbersome, the synthesis is complex, and the process requirements are high, which is not suitable for large-scale industrial production.
[0004] Therefore, there is a need in the art to develop an adhesive that can achieve adhesion in underwater or wet environments and does not rely on chemical synthesis or molecular modification, and that can overcome the influence of water film on the adhesion effect in underwater environments. Summary of the invention
[0005] In view of the problems of the prior art, the present invention provides a liquid adhesive, which comprises the following components:
[0006] (I) a solvent miscible with water; the dielectric constant of the solvent is ≥30°C 2 / (N·m 2 );
[0007] (II) high molecular weight polymer;
[0008] (III) underwater adhesion molecules;
[0009] (IV) a metal ion compound capable of coordinating with a polymer compound and an underwater adhesion molecule;
[0010] The ratio of the Marangoni number in the horizontal direction to the Marangoni number in the vertical direction of the liquid adhesive is greater than 1 (eg, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, etc.).
[0011] The calculation formula of Marangoni number is:
[0012]
[0013] Among them, μ l is the viscosity of the adhesive, D l is the molecular diffusion coefficient of the adhesive; δ γ / δ C is the surface tension gradient of the adhesive in water as the concentration changes; ΔC is the concentration change when the adhesive diffuses unstably in water; L is the distance the adhesive moves in the horizontal or vertical direction.
[0014] The Marangoni number ratio characterizes the spreading state of the adhesive underwater. When it is greater than or equal to 1, the larger the value, the better the spreading property; when it is greater than 0 and less than 1, the force in the vertical direction is greater than the force in the horizontal direction, and the adhesive diffuses into the water; when it is 0, it does not spread and is spherical.
[0015] The dielectric constant of the water-miscible solvent is ≥30, which can ensure that the liquid adhesive can expel the water film on the adhesion surface in an underwater or wet environment, quickly infiltrate and spread, and can stably exist on the adhesion surface, and the underwater adhesion performance is significantly improved with the extension of the standing time. For non-polar solvents with very low dielectric constants (such as dielectric constants <10C 2 / (N·m 2 )), the liquid adhesive prepared by the method is spherical and anti-wetting in water, and has no viscosity; and for medium polar solvents with medium dielectric constants (such as medium dielectric constants between 10 and 30 °C 2 / (N·m 2 ), the prepared liquid adhesive will quickly diffuse into the aqueous phase underwater and cannot remain on the solid surface, and also has no adhesion properties.
[0016] When the ratio of the Marangoni number in the horizontal direction to the Marangoni number in the vertical direction of the liquid adhesive is ≥1, the liquid adhesive has obvious spreadability underwater and can cover the target substrate.
[0017] The present invention selects a dielectric constant ≥ 30C 2 / (N·m 2 ) is used as a dispersant for the liquid adhesive, and the high molecular polymer and the underwater adhesion molecules are dispersed in the solvent to obtain a liquid adhesive with a ratio of the horizontal Marangoni number to the vertical Marangoni number greater than 1, thereby achieving the expulsion of the water film on the adhesion surface, providing a channel for the high molecular polymer and the underwater adhesion molecules to adhere to the adhesion surface, and achieving adhesion to the adhesion surface in an underwater or wet environment.
[0018] Preferably, the surface tension of the water-miscible solvent is ≥33 mN / m, for example, 34 mN / m, 36 mN / m, 38 mN / m, 40 mN / m, 43 mN / m, 46 mN / m, 48 mN / m, 55 mN / m, 60 mN / m, 68 mN / m and the like.
[0019] Since the surface tension of polar solvents with high dielectric constants is lower than that of water, they can adjust the surface energy of liquid adhesives, forming a surface energy gradient with the water layer on the solid surface, thereby inducing turbulent motion of the liquid-liquid interface between the liquid adhesive and water, achieving the infiltration and spreading of the liquid adhesive on the underwater solid surface, and promoting full contact between the adhesion molecules and the solid surface while expelling the water layer. At the same time, due to the mutual solubility of such solvents with water, as the liquid adhesive is left to stand underwater for a longer time, it will produce an exchange with the water phase from top to bottom, thereby triggering the ionization of the internal components of the liquid adhesive, achieving the coordination of high molecular polymers, underwater adhesion molecules and metal ions, and forming a network-like porous structure, thereby enhancing the underwater adhesion performance of the liquid adhesive.
[0020] Preferably, the diffusion coefficient of the water-miscible solvent in water is ≤0.9×10 -5 cm 2 s, for example 0.8×10 -5 cm 2 ·s, 0.7×10 -5 cm 2 ·s, 0.6×10 -5 cm 2 ·s, 0.5×10 -5 cm 2 ·s, 0.4×10 -5 cm 2 ·s, 0.3×10 -5 cm 2 ·s, 0.2×10 -5 cm 2 ·s, 0.1×10 -5 cm 2 ·s, etc.
[0021] The diffusion coefficient of the water-miscible solvent in water is ≤0.9×10 -5 cm 2 ·s can reduce the time for the solvent to diffuse into the water and prolong the contact time of the adhesion molecules on the solid surface. If it is greater than 0.9×10 -5 cm 2 ·s, which will cause the solvent to detach from the adhesion molecules and diffuse rapidly into the water.
[0022] Preferably, the density of the water-miscible solvent is 0.8 to 1.2 g / cm 3, for example 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 wait.
[0023] The density of the water-miscible solvent is 0.8-1.2 g / cm 3 The purpose of preventing the adhesive from floating upward can be achieved if the density of the water-miscible solvent is lower than 0.8 g / cm 3 , the liquid adhesive will easily float up to the water surface quickly, thus affecting the adhesion performance.
[0024] Preferably, the water-miscible solvent includes any one of dimethyl sulfoxide, hexamethylphosphoramide, formamide or N,N-dimethylformamide, or a combination of at least two thereof.
[0025] Preferably, in the liquid adhesive, the mass ratio of the water-miscible solvent to the underwater adhesion molecules is 8.8:1 to 55:1 (for example, 8.9:1, 11:1, 14:1, 18:1, 23:1, 28:1, 30:1, 35:1, 38:1, 40:1, 41:1, 45:1, 47:1, 48:1, 50:1, 53:1, etc.), preferably 43:1 to 46:1, and more preferably 44:1.
[0026] In the liquid adhesive, the underwater adhesion molecules are complexed with metal ions and form an interpenetrating network with the high molecular polymer. The mass ratio of the water-miscible solvent to the underwater adhesion molecules is between 8.8 and 55, which can achieve a good wetting, spreading and adhesion effect on the surface to be bonded. If the mass ratio is lower than 8.8, the solvent content is low, and the underwater adhesion molecules and high molecular polymer content of the adhesive are high, resulting in the dispersed components of the adhesive (underwater adhesion molecules and high molecular polymers) diffusing faster into the water, and it is difficult to crosslink and solidify to achieve adhesion on the underwater solid surface. If the mass ratio is higher than 55, the solvent content is high, a large amount of solvent diffuses into the water, and it is more difficult for the adhesion molecules to spread on the solid surface, and the adhesion performance is poor; when the mass ratio of the water-miscible solvent to the underwater adhesion molecules is between 43:1 and 46:1, the solvent can expel the water layer and achieve the effect of wetting and spreading.
[0027] As a preferred technical solution, the underwater adhesion molecules include compounds connected with catechol groups and / or dopamine groups.
[0028] The catechol group can be understood as catechol bonded to the parent molecule via a single bond, a substituted or unsubstituted amine group, or a substituted or unsubstituted alkyl group; the dopamine group can be understood as dopamine bonded to the parent molecule via a single bond, a substituted or unsubstituted amine group, or a substituted or unsubstituted alkyl group. The parent molecule is exemplarily a polymer backbone, and typical but not limiting examples thereof include high molecular weight polymers such as polystyrene, polyacrylamide, polyacrylic acid, and polyvinyl alcohol.
[0029] The catechol group and / or dopamine group can coordinate with metal ions in an underwater or wet environment to achieve cross-linking and bonding.
[0030] Preferably, the underwater adhesion molecule comprises any one of a polymer grafted with dopamine groups, a polymer grafted with dopa, tannic acid or a tannic acid derivative, or a combination of at least two thereof, preferably tannic acid.
[0031] It should be noted that when the underwater adhesion molecule is selected to have a dopamine group or a dopa group, it is best to graft the dopamine or dopa onto a polymer to increase the content of the phenolic hydroxyl group and the molecular weight.
[0032] The present application uses tannic acid as the underwater adhesion molecule, which improves the antioxidant properties of the liquid adhesive, expands the application range of the liquid adhesive, and can expand the pH value range of the liquid adhesive to 2 to 12, thereby expanding the pH application range of the liquid adhesive.
[0033] As a preferred technical solution, the high molecular polymer is a high molecular polymer that can be stably dispersed in the solvent miscible with water.
[0034] The high molecular polymer described in the present invention is a high molecular polymer that can stably exist in the solvent miscible with water, which can ensure that the high molecular polymer is evenly and stably dispersed in the liquid adhesive, and remains stable when the adhesive is infiltrated and spread on the underwater solid surface, thereby promoting full contact between the adhesion molecules and the solid surface.
[0035] Preferably, the high molecular polymer comprises an ionic high molecular polymer, preferably an anionic high molecular polymer.
[0036] The ionic high molecular polymer includes any one of anionic high molecular polymer and cationic high molecular polymer or a combination of at least two of them.
[0037] Preferably, the high molecular polymer is connected with any one of carboxyl, thiol, hydroxyl and amino groups or a combination of at least two of them.
[0038] Preferably, the high molecular polymer includes any one of polyacrylic acid, polyvinyl pyrrolidone, polyacrylamide, and polyvinyl alcohol, or a combination of at least two thereof.
[0039] Among them, polyvinyl pyrrolidone is a good stabilizer and can have a good coordination and cross-linking effect with metal ions, especially iron ions, and can also be well dispersed in the selected polar solvent.
[0040] Preferably, in the liquid adhesive, the mass ratio of the high molecular polymer to the underwater adhesion molecule is 0.03:1 to 16:1 (for example, 0.05:1, 0.8:1, 1:1, 3:1, 4:1, 6:1, 9:1, 11:1, 13:1, 15:1, etc.), preferably 6:1 to 9:1, and more preferably 8:1.
[0041] High molecular weight polymers can improve the adhesion firmness of underwater adhesion molecules, but too high a high molecular weight polymer content (for example, greater than 16:1) will lead to a decrease in adhesion performance.
[0042] In a preferred technical solution, the metal ions of the metal ion compound include any one or a combination of at least two of ferric ions, ferrous ions, copper ions, nickel ions, calcium ions, magnesium ions, silver ions, platinum ions and zinc ions, preferably ferric ions.
[0043] Metal ions play a role in coordinating and cross-linking with underwater adhesion molecules, and trivalent iron ions have the strongest coordination effect, which can better promote underwater adhesion performance. When other metal ions (such as divalent iron ions, copper ions, nickel ions, calcium ions, magnesium ions, silver ions, platinum ions and zinc ions) are selected, better adhesion effects can be obtained by increasing the amount of adhesion molecules added.
[0044] Preferably, in the liquid adhesive, the mass ratio of the metal ion compound to the underwater adhesion molecule is 0.3:1 to 3:1, preferably 0.7:1 to 0.8:1, and more preferably 0.76:1.
[0045] When the mass ratio of the metal ion compound to the underwater adhesive molecule is 0.3:1 to 3:1, a good underwater spreading and adhesion effect can be achieved. When it is higher than 3:1, agglomeration is likely to occur, reducing the adhesion performance. When it is lower than 0.3:1, there is a certain possibility that the underwater adhesive will lose its adhesion.
[0046] Preferably, the ratio of the Marangoni number in the horizontal direction to the Marangoni number in the vertical direction of the liquid adhesive is ≥4.
[0047] When the ratio of the Marangoni number in the horizontal direction to the Marangoni number in the vertical direction of the liquid adhesive is ≥4, the liquid adhesive has good spreadability underwater and can achieve good coverage of the target substrate.
[0048] The second object of the present invention is to provide a method for preparing the liquid adhesive as described in the first object, the preparation method comprising the following steps:
[0049] The liquid adhesive is obtained by adding a high molecular polymer, underwater adhesive molecules and a metal ion compound into a solvent miscible with water and stirring the mixture.
[0050] Preferably, the method is carried out at normal temperature and pressure.
[0051] Preferably, the stirring speed is 400-1000 rpm, preferably 400 rpm, 500 rpm, 600 rpm, 800 rpm, 1000 rpm, etc.
[0052] Preferably, the stirring time is 4 to 24 hours (eg, 6 hours, 12 hours, 15 hours, 18 hours, 20 hours, 23 hours, etc.), preferably 6 to 10 hours, and more preferably 6 hours.
[0053] Appropriate stirring speed and stirring time can obtain liquid adhesive more quickly.
[0054] The third object of the present invention is to provide a use of the liquid adhesive as described in the first object, wherein the liquid adhesive is used to adhere materials in an underwater medium environment.
[0055] The liquid adhesive provided by the present invention selects a suitable solvent as a dispersion medium, in which a high molecular polymer, underwater adhesion molecules and metal ion compounds are dispersed. The liquid adhesive generates turbulence at the liquid-liquid interface in an underwater or water-wet environment, causing the liquid adhesive to infiltrate and spread on the underwater solid surface, and while expelling the water layer, promotes full contact between the adhesion molecules and the solid surface to achieve adhesion.
[0056] As one of the preferred technical solutions, the step of adhering the liquid adhesive in an underwater medium environment comprises:
[0057] (S10) applying the liquid adhesive on a target substrate underwater to obtain a target substrate coated with the adhesive;
[0058] (S20) Adhere the attaching substrate to the target substrate coated with the adhesive, and let it stand to complete the bonding of the target substrate and the attaching substrate.
[0059] As a second preferred technical solution, the step of adhering the liquid adhesive in an underwater medium environment comprises:
[0060] (T10) coating the liquid adhesive on an attachment substrate to obtain an attachment substrate coated with a single-component adhesive;
[0061] (T20) Adhere the adhesive-coated attachment substrate to the underwater target substrate and allow it to stand to complete the bonding of the target substrate and the attachment substrate.
[0062] As a third preferred technical solution, the step of adhering the liquid adhesive in an underwater medium environment comprises:
[0063] (K1) bringing the attachment substrate and the target substrate close to each other with a gap between them, and injecting the liquid adhesive into the gap;
[0064] (K2) Extruding the attachment substrate and the target substrate, and letting them stand to complete the bonding of the target substrate and the attachment substrate.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] (1) The present invention provides a liquid adhesive that can be used underwater or in a wet environment, which can achieve adhesion to the target object in an underwater or wet environment, overcoming the difficulty of adhesion caused by the presence of a water film on the surface of the bonding object; at the same time, the present invention uses high molecular polymers and underwater adhesion molecules, which are coordinated under the action of metal ions to form an interpenetrating network, thereby achieving a strong adhesion effect in an underwater or wet environment.
[0067] (2) In the preferred technical solution, the present application uses tannic acid as the underwater adhesion molecule, which improves the antioxidant properties of the liquid adhesive, expands the applicable scope of the liquid adhesive, and can expand the pH value range of the liquid adhesive to 2 to 12, thereby expanding the pH applicable range of the liquid adhesive.
[0068] (2) The present invention also provides the use of the liquid adhesive, which, as mentioned above, can achieve adhesion to a target object underwater or in a wet environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 Observation diagram of the adhesion performance of the underwater adhesive of Comparative Example 3, Comparative Example 1 and Example 1;
[0070] Figure 2 This is a graph showing the Marangoni number ratios of the underwater adhesives of Example 1, Comparative Example 1 and Comparative Example 3. DETAILED DESCRIPTION
[0071] The technical solution of the present application is further illustrated below through specific implementation methods.
[0072] Those skilled in the art should understand that the embodiments are only to help understand the present application and should not be regarded as specific limitations of the present application.
[0073] Example 1
[0074] A liquid adhesive is prepared by the following method:
[0075] A high molecular polymer, underwater adhesion molecules, and a metal ion compound are added to a solvent miscible with water, and the mixture is stirred to obtain the liquid adhesive; wherein the addition amount of each component is shown in Table 1.
[0076] Table 1-1
[0077]
[0078] Note: ① In Table 1-1, the weight average molecular weight of polyacrylic acid is 400,000 to 500,000, and the weight average molecular weight of polyvinyl pyrrolidone is 400,000 to 500,000.
[0079] ② In Table 1-1, the amount of each component added is in parts by weight.
[0080] Table 1-2
[0081]
[0082] Note: ① In Table 1-2, the weight average molecular weight of polyacrylic acid is 400,000 to 500,000, and the weight average molecular weight of polyvinyl pyrrolidone is 400,000 to 500,000.
[0083] ② In Table 1-2, the amount of each component added is in parts by weight.
[0084] Application Examples
[0085] A glass slide, an aluminum sheet, a stainless steel sheet, a polystyrene sheet, or a polytetrafluoroethylene sheet is placed as a target substrate in an underwater environment, and the liquid adhesive obtained in the embodiments and application examples is adhered according to the following method to achieve adhesion to the target substrate:
[0086] (S10) applying the liquid adhesive on a target substrate underwater to obtain a target substrate coated with the adhesive;
[0087] (S20) Adhere the attaching substrate to the target substrate coated with the adhesive, and let it stand to complete the bonding of the target substrate and the attaching substrate.
[0088] Performance Test:
[0089] The target substrate with the adhesive substrate is subjected to the following performance tests:
[0090] (1) Adhesion performance: A glass slide was placed underwater as the target substrate, and then the prepared liquid adhesive was injected onto the surface of the target substrate. Then, another target substrate was placed as the upper surface in contact with the target substrate surface at the bottom of the water. After standing for a period of time, the substrate was pulled upward to test the adhesion between the upper and lower solid surfaces.
[0091] In order to observe and compare the adhesion performance more intuitively, the liquid adhesive was applied between two plastic gloves under water, and a pulling force was applied to separate them. The state of the liquid adhesive between the two gloves was observed over time. The observation results are as follows: Figure 1 ( Figure 1 Observation diagram of the adhesion performance of the liquid adhesives of Comparative Example 3, Comparative Example 1 and Example 1), Figure 1 The samples from top to bottom are the liquid adhesive of comparative example 3 in the first row, comparative example 1 in the second row, and example 1 in the third row;
[0092] (2) Ratio of the Marangoni number of the liquid adhesive in the horizontal direction to the Marangoni number in the vertical direction: Underwater dynamic monitoring is used to record the distances moved by the prepared underwater adhesive in the two directions perpendicular to the underwater solid surface and along the underwater solid surface at different times, and the corresponding formulas are used to calculate the Marangoni number in the horizontal direction and the Marangoni number in the vertical direction, and finally the ratio of the Marangoni number in the horizontal direction to the Marangoni number in the vertical direction is calculated. Figure 2 A Marangoni number ratio graph of the liquid adhesives of Example 1, Comparative Example 1 and Comparative Example 3 is given.
[0093] Combination Figure 1 and Figure 2 It can be seen that the liquid adhesive provided by Example 1 of the present invention has good spreadability and good adhesion performance underwater; Comparative Example 1 (the solvent is ethanol) quickly diffuses into the water and cannot achieve adhesion; Comparative Example 3 (the solvent is benzyl alcohol) is spherical underwater and cannot achieve adhesion; Figure 2 The samples from top to bottom are the underwater adhesives of Example 1, Comparative Example 1 and Comparative Example 3.
[0094] The test results are shown in Table 2
[0095] Table 2
[0096]
[0097]
[0098] It shows that when the Marangoni number ratio is ≥1, the larger the value, the better the spreading property; when 0<Marangoni number ratio<1, it diffuses into the water; when Marangoni number ratio = 0, it does not spread and is spherical.
[0099] It can be seen from Table 2 and Examples 1 to 5 that when the amount of the solvent miscible with water is between 8.8 and 55 parts by weight, the peel strength is relatively high, all within 0.128 N / cm 2When the amount of solvent added is less than 8.8 parts by weight (Example 4), the adhesive content increases, which leads to a proper increase in the bonding strength of the entire adhesive, but it still cannot reach the optimal bonding strength of 44 parts by weight of solvent content; when the amount of solvent added is greater than 55 parts by weight (Example 5), the bonding strength of the adhesive tends to decrease, but it still has obvious adhesion. As can be seen from Examples 6 to 8, the solvent can also be selected from hexamethylphosphoramide (Example 6), formamide (Example 7) and N,N-dimethylformamide (Example 8), and formamide has the best effect, with an adhesion of 1.4N / cm 2 The second is dimethyl sulfoxide, whose adhesion is 0.726N / cm 2 Above, followed by N,N-dimethylformamide and hexamethylphosphoramide, and the Marangoni number ratios are all above 2, and have a certain spreadability underwater. It can be seen from Example 1 and Examples 9 to 11 that although the adhesion is not very high, the Marangoni number ratios are all above 4, showing good spreadability. That is, when the content of the high molecular polymer is too low (0.01 parts by weight), the adhesive shows good spreadability, but the bonding strength needs to be improved. When the content of the high molecular polymer is too high (greater than 16 parts by weight), the adhesive also shows good spreadability, but the bonding strength also needs to be improved. It can be seen from Example 1 and Examples 12 to 15 that they all have good spreadability (the Marangoni number ratios are all above 4). From the perspective of bonding strength, 0.3 to 3 parts by weight of ferric chloride can obtain a higher bonding strength (at 0.058N / cm 2 When the weight is less than 0.3 parts by weight or greater than 3 parts by weight, the bonding strength decreases significantly (at 0.054 N / cm 2 In addition, it can be seen from Example 16 that the high molecular polymer can also be selected from other polymers besides polyacrylic acid, such as polyvinyl pyrrolidone, which has a bonding strength similar to or even better than that of polyacrylic acid and has better spreadability.
[0100] It can be seen from the comparative data in Table 2 that the dielectric constants of ethanol, tetrahydrofuran and benzyl alcohol are less than 30. Compared with solvents with a dielectric constant ≥ 30, the adhesion strength and spreadability of the obtained adhesive are reduced. For example, when ethanol is selected as the solvent in Comparative Example 1, its diffusivity is too strong (Marangoni number ratio 0.62), and it quickly diffuses into the medium and cannot achieve adhesion; when tetrahydrofuran is selected as the solvent in Comparative Example 2, the dispersibility of each component is poor, and a uniformly dispersed adhesive cannot be formed; when benzyl alcohol is selected as the solvent in Comparative Example 3, its spreadability is very poor (Marangoni number ratio 0), and it is spherical. Although it has a strength of 0.056 N / cm 2The adhesion test value is 1.0, but it is essentially a liquid bridge effect and cannot produce effective adhesion with the substrate. The polymer can enhance the cohesion of the adhesive body and enhance the effect with the substrate. If the polymer is not added, such as in Comparative Example 4, although it has good spreadability, it will cause a significant decrease in adhesion.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A liquid adhesive, characterized in that: The liquid adhesive comprises the following components: (I) a solvent miscible with water, the dielectric constant of the solvent being greater than 30°C 2 / (N·m 2 ), surface tension ≥33mN / m, density 0.8~1.2g / cm 3 , the diffusion coefficient of the solvent in water is ≤0.9×10 -5 cm 2 ·s; (II) high molecular weight polymer; (III) underwater adhesion molecules; (IV) a metal ion compound capable of coordinating with a polymer compound and an underwater adhesion molecule; Wherein, the water-miscible solvent includes formamide, the underwater adhesion molecule includes any one or a combination of at least two of a polymer grafted with dopamine groups, a polymer grafted with dopa, tannic acid or a tannic acid derivative, and the high molecular polymer includes any one or a combination of at least two of polyvinyl pyrrolidone, polyacrylamide, and polyvinyl alcohol; The mass ratio of the solvent to the underwater adhesion molecules is 8.8:1 to 55:1, the mass ratio of the metal ion compound to the underwater adhesion molecules is 0.3:1 to 3:1, and the mass ratio of the high molecular polymer to the underwater adhesion molecules is 0.02:1 to 16:1; The ratio of the Marangoni number in the horizontal direction to the Marangoni number in the vertical direction of the liquid adhesive is greater than 1.
2. The liquid adhesive according to claim 1, characterized in that In the liquid adhesive, the mass ratio of the water-miscible solvent to the underwater adhesive molecules is 43:1 to 46:
1.
3. The liquid adhesive according to claim 1, characterized in that The underwater adhesion molecules include tannic acid.
4. The liquid adhesive according to claim 1, characterized in that In the liquid adhesive, the mass ratio of the high molecular polymer to the underwater adhesion molecule is 6:1 to 9:
1.
5. The liquid adhesive according to claim 1, characterized in that The metal ions of the metal ion compound include any one of ferric ion, ferrous ion, copper ion, nickel ion, calcium ion, magnesium ion, silver ion, platinum ion and zinc ion, or a combination of at least two of them.
6. The liquid adhesive according to claim 1, characterized in that The mass ratio of the metal ion compound to the underwater adhesion molecule is 0.7:1 to 0.8:
1.
7. The liquid adhesive according to claim 1, characterized in that The ratio of the Marangoni number in the horizontal direction to the Marangoni number in the vertical direction of the liquid adhesive is ≥4.
8. A method for preparing a liquid adhesive according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The liquid adhesive is obtained by adding a high molecular polymer, underwater adhesive molecules and a metal ion compound into a solvent miscible with water and stirring the mixture.
9. The preparation method according to claim 8, characterized in that: The preparation method comprises the following steps: A high molecular polymer, underwater adhesive molecules and metal ion compounds are added to a solvent miscible with water, and stirred at room temperature and pressure to obtain the liquid adhesive; the stirring speed is 400 to 1000 revolutions per minute, and the stirring time is 4 to 24 hours.
10. Use of the liquid adhesive according to any one of claims 1 to 9, characterized in that: The liquid adhesive is used for adhering materials in an underwater medium environment.
11. The use according to claim 10, characterized in that The step of adhering the liquid adhesive in an underwater medium environment comprises: (S10) applying the liquid adhesive on a target substrate underwater to obtain a target substrate coated with the adhesive; (S20) adhering the attaching substrate to the target substrate coated with the adhesive, and allowing the substrate to stand to complete the bonding of the target substrate and the attaching substrate; Alternatively, the step of adhering the liquid adhesive in an underwater medium environment comprises: (T10) coating the liquid adhesive on an attachment substrate to obtain an attachment substrate coated with a single-component adhesive; (T20) adhering the adhesive-coated attachment substrate to the underwater target substrate and allowing the target substrate to stand to complete the bonding between the target substrate and the attachment substrate; Alternatively, the step of adhering the liquid adhesive in an underwater medium environment comprises: (K1) bringing the attachment substrate and the target substrate close to each other with a gap between them, and injecting the liquid adhesive into the gap; (K2) Extruding the attachment substrate and the target substrate, and letting them stand to complete the bonding of the target substrate and the attachment substrate.
Citation Information
Patent Citations
Single-component bionic mussel adhesive and wet surface and underwater construction method through phase separation
CN109762492A